Human Capital and Income Inequality Linkage in Sub- Saharan Africa: Panel Data Analysis (1984–2016) - Molla, Gashaw Getaye (Journal of Developing Economies, 2021)
Income inequality means that one segment of the population has a disproportionately large share of income compared to the other. Disparities in income and wealth have tended to dominate the discussion on inequality because they contribute directly to individuals and families' well-being and shape the opportunities people have in life. Therefore, addressing income inequality is essential to inspire each country's population's human and productive potentials to bring development. Therefore, this study examines the relationship between income inequality and human capital using static panel data analysis. Specifically, the study employs fixed effect panel data analysis using Least Square Dummy Variable for 25 sub-Saharan African countries. The World Bank data series was widely used as the data source for macroeconomic variables, while the Gini index has obtained from the Standardized World Income Inequality Database. The empirical results reveal that human capital in terms of secondary school enrollment rate has a negative impact on income inequality. The study also found a U-shaped relationship between real gross domestic product per capita and inequality, and it does not support the well-known concept of the Kuznets curve.Keywords: Income Inequality; Human Capital; Panel Data; Random Effect; Fixed Effect.JEL: C10, Q0, A10